PENGARUH PENGETAHUAN PAJAK DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Supriyanti; Nur Hidayati (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2008)
The Directorate General of Taxation has been done strategic role as one of steps to increase the tax payer's compliance. This research attempts to see the influence of tax knowledge, tax payer perception of fiscus and criterions of tax payer of compliance toward tax payer compliance. The procedure of data collection in this research is by distributing the questionnaire to the tax payer in Tax Service Department East Sidoarjo directly at 2007. There are 43 questioners collected. The result of validity and reliability from 44 question shows that all question is valid and reliable. So, the result of normality shows that data is normal distribution. The result of regression shows that just tax knowledge variable influence significantly toward tax payer compliance.